Putting Prosody First — Some Practical Solutions to a Perennial Problem: The Innovalangues Project - Frost, Dan; Picavet, Francis (Research in Language, 2014)
This paper presents some of the difficulties of teaching languages, in particular English, in the context of LSP/LAP2 programmes in French universities. The main focus of this paper will be the importance of prosody, especially in English, as an area where these difficulties may be addressed. We will outline the various solutions that are currently being put into place as part of the Innovalangues project, a six-year international language teaching and research project headed by Université Stendhal (Grenoble 3), France. The project has substantial funding from the French Ministry of Higher Education and Research and its mission is to develop innovative tools and measures to help LSP/LAP learners reach B2 on the Common European Framework of Reference for Languages (CEFRL). The languages concerned are English, Italian, Spanish, Chinese, Japanese and possibly French as a foreign language. Initially the project will be focusing on the needs of Grenoble’s students, but the objective is to make the tools and resources developed freely available to the wider community. Oral production and reception are at the heart of Innovalangues. We believe, along with many other researchers, that prosody is key to comprehension and to intelligibility (Kjellin 1999a, Kjellin 1999b, Munro and Derwing 2011, Saito 2012), particularly given the important differences between English and French prosody (Delattre 1965; Hirst and Di Cristo 1998; Frost 2011). In this paper, we will present the particular difficulties inherent in teaching English (and other foreign languages) in the context of ESP/EAP3 in French universities and some of the solutions that we are implementing through this project (Picavet et al., 2012; Picavet et al 2013; Picavet and Frost 2014). These include an e-learning platform for which various tools are being developed, teacher training seminars focusing on prosody and the collection of data for research.